Reduction of nosocomial infections in the intensive care unit using an electronic hand hygiene compliance monitoring system - GÜL, FETHİ; YAKUT, NURHAYAT; BİLGİLİ, BELİZ; KASAPOĞLU, UMUT SABRİ; ARSLANTAŞ, MUSTAFA KEMAL; KEPENEKLİ KADAYİFCİ, EDA (My University, 2021)
Introduction: Healthcare-associated infection is an important cause of mortality and morbidity worldwide. Well-regulated infection control and hand hygiene are the most effective methods for preventing healthcare-associated infections. This study evaluated and compared conventional hand hygiene observation and an electronic hand-hygiene recording and reminder system for preventing healthcare-associated infections. Methodology: This pre-and post-intervention study, employed an electronic hand-hygiene recording and reminder system for preventing healthcare-associated infections at a tertiary referral center. Healthcare-associated infection surveillance was recorded in an anesthesia and reanimation intensive care unit from April 2016 to August 2016. Hand-hygiene compliance was observed by conventional observation and an electronic recording and reminder system in two consecutive 2-month periods. healthcare-associated infections were calculated as incidence rate ratios. Results: The rate of healthcare-associated infections in the electronic hand-hygiene recording and reminder system period was significantly decreased compared with that in the conventional hand-hygiene observation period (incidence rate ratio = 0.58; 95% confident interval = 0.33-0.98). Additionally, the rate of central line-associated bloodstream infections and the rate of ventilator-associated pneumonia were lower during the electronic hand hygiene recording and reminder system period (incidence rate ratio= 0.41; 95% confident interval = 0.11-1.30 and incidence rate ratio = 0.67; 95% confident interval = 0.30-1.45, respectively). Conclusions: After implementing the electronic hand hygiene recording and reminder system, we observed a significant decrease in healthcare-associated infections and invasive device-associated infections. These results were encouraging and suggested that electronic hand hygiene reminder and recording systems may reduce some types of healthcare-associated infections in healthcare settings.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; BULAŞICI HASTALIKLAR; İmmünoloji; Yaşam Bilimleri (LIFE); INFECTIOUS DISEASES; IMMUNOLOGY; Life Sciences (LIFE); Bulaşıcı hastalıklar; Genel İmmünoloji ve Mikrobiyoloji; Sağlık Bilimleri; Infectious Diseases; Immunology; General Immunology and Microbiology; Health Sciences; Electronic hand hygiene recording and reminder system; healthcare-associated infection; hand hygiene; compliance